Bleeding Times in Rats Treated with Heparin, Heparin Fragments of High and Low Anticoagulant Activity and chemically Modified Heparin Fragments of Low Anticoagulant Activity - Palm, Maud; Mattsson, Christer; Svahn, Carl Magnus; Weber, Michael (Thrombosis and Haemostasis, 1990)
A template bleeding time study in the rat was undertaken to see if it is possible to correlate bleeding times with the molecular weight, anticoagulant activity or chemical composition of heparin or heparin-derived compounds. Heparin from porcine intestinal rnucosa (PM-heparin) and from bovine lung (BL-heparin) as well as heparin fragments from these sources were compared. Heparin fragments of low anticoagulant activity were prepared by affinity chromatography on immobilized antithrombin as well as by chemical modification. A heparin fragment of high affinity for antithrombin (HA-fragment) caused a marked and dose-dependent increase in bleeding time while the corresponding heparin fragment with low affinity for antithrombin (LA-frugment) had a marginal and non-dose dependent effect on the bleeding time. Similar results were also obtained with PM-heparin with high and low affinity for antithrombin. A high anti-FXa activity was not always correlated with a marked bleeding tendency. Provided that a fragment was devoid of activated partial thromboplastin time (APTT) activity, it was not possible to provoke a bleeding time of 20 min or longer, although the compound was administered at a dose of 1,088 U/kg (anti-FXa activity). On the other hand, & Nacetylated chemically oversulphated heparin fragment, with a very low anti-FXa activity (1 U/mg) and with an APTT activity of 34UlmtB, caused a bleeding time of 20 min or longer in 70% of the animals after injection of the same number of Aprr units, 1,088 U/kg. These data indicate that the APTT activity is a better and more sensitive indicator of the bleeding than is the anti-FXa activity.